Few-layered MoS2 nanosheets wrapped ultrafine TiO2 nanobelts with enhanced photocatalytic property. Issue 11 (2nd March 2016) - Li, Haidong; Wang, Yana; Chen, Guohui; Sang, Yuanhua; Jiang, Huaidong; He, Jiating; Li, Xu; Liu, Hong
Abstract : A heterostructured photocatalyst comprised of few-layered MoS2 nanosheets coated on a TiO2 nanobelts surface was synthesized through a simple hydrothermal treatment. Abstract : Photocatalytic materials comprised of semiconductor nanostructures have attracted tremendous scientific and technological interest over the last 30 years. This is due to the fact that these photocatalytic materials have unique properties that allow for an effective direct energy transfer from light to highly reactive chemical species which are applicable in the remediation of environmental pollutants and photocatalytic hydrogen generation. Heterostructured photocatalysts are a promising type of photocatalyst which can combine the properties of different components to generate a synergic effect, resulting in a high photocatalytic activity. In this work, a heterostructured photocatalyst comprised of few-layered MoS2 nanosheets coated on a TiO2 nanobelts surface was synthesized through a simple hydrothermal treatment. The hybrid heterostructures with enhanced broad spectrum photocatalytic properties can harness UV and visible light energy to decompose organic contaminants in aqueous solutions as well as split water to hydrogen and oxygen. The mechanism of the enhancement is that the MoS2 /TiO2 nanobelts heterostructure can enhance the separation of the photo-induced carriers, which results in a higher photocurrent due to the special electronic characteristics of the graphene-like layered MoS2 nanosheets. This methodology is potentially applicable to the synthesis of a range of hybrid nanostructures with promising applications in photocatalysis and other relevant areas.